Electrohydrodynamic Drying in Agribusiness: Literature Review - Ciprian Foronda, Kevin Daniel; Gafaro Garcés, Delcy Camila; Restrepo Rendón, Laura; Mendoza Alvites, Yeyner Yamphier; Ricardo Sagra, Joana Paola; Orozco Mendoza, Gina Lia; Zartha Sossa, Jhon Wilder (Frontiers in Sustainable Food Systems, 2022)
In agribusiness, drying is a unitary operation that optimizes the production and preservation of products and raw materials. Drying is performed through different traditional methods, one of the most recently studied is the electrohydrodynamic drying EHD which uses an electric field that allows decreasing the processing time thus increasing the drying speed of raw materials and consuming less energy. In this article, a review was carried out through Scopus using a search equation with the keywords “Electrohydrodynamic drying,” “food” and “AGRI” which resulted in a total of 145 articles; which were analyzed through in-depth reading, analyzing aspects such as year, author, keywords, countries, quartile, journal, relationship with agroindustry, mathematical models used and applications in agro-industrial products, this analysis was complemented with the application of Vantage Point software through co-occurrence matrices and cluster analysis. Recent applications were found in Carrot, Chicken, Sea Cucumber, Goji Berry, Peppermint Leaf, Quince, Potato, Blueberry, Aquatic Products, Banana Slices, Grape Pomace, Blueberry, Apple, Mushroom, Wheat, and Mushroom Slices, mathematical models with application in EHD drying were also found, such as Henderson and Pabis, Page, Logarithmic, Quadratic, Newton/Lewis, Diffusion and exponential.